Sadiq and the green thumbs - Nuurali, Siman (Nuurali, Siman. Sadiq., 2020)
Even though it is summer Sadiq goes to religious school four days a week to study the Quran; he and his friends find their teacher, Mr. Kassim, strict and intimidating, but when Sadiq finds out that Mr. Kassim has a injured shoulder he decides to volunteer to help with the gardening--and he convinces his friends to volunteer as well.